PELAKSANAAN MODEL PEMBELAJARAN TRANSPARAN DI JURUSAN TEKNIK ELEKTRONIKA UNIVERSITAS NEGERI YOGYAKARTA - Sarbiran Sarbiran (Universitas Negeri Yogyakarta, 2002)
Abstract A teaching model is a special method, something that lecturers can apply. It may improve the educational quality and satisfaction of both students and lecturers, but what kinds of teaching model and its alternative should be implied. This research will answer the questions. The study was also aimed to reveal: (1) lecturers’ perception of the transparent teaching model and (2) the contingency correlation between lecturers’ rank and the transparent teaching model to be used. The study was conducted from June to November 2002. The population of the study was all lecturers at the Department of Electronics (18 from the 22 lecturers was the respondents), Faculty of Technology, Yogyakarta State University. Questionnaires and interview guide were the instrument of the study. The data analysis techniques employed was: descriptive and non-parametric statistics (X2). The result of the study shows that: (1) a transparent teaching model (TTM) was needed as the teaching model for electronic education; (2) there is low contingency correlation between lecturers’ rank and the transparent teaching model (C=0.28 low compared to C max =0.82). Transparent means clear, obvious, complete, satisfactory, professional, doubtless, and error free. There are five kinds of TTMs appropriate for the Department of Electronics: (1) Theoretical TTm; (2) Laboratory TTM;(3)Workshop TTm; (4) Student Individual Study; and (5) Lecturers’ job assignment. Possibly some models have been used by the lecturers, while others have not. A further study is necessary for looking at the advantages and the disadvantages of the models. Keywords: teaching model, transparent teaching model, and special method.